Pengalaman Remaja Pengguna Aktif Twitter dalam Membangun Komunitas Virtual sebagai Ruang Aman (Safe Space) : Penelitian - Nova Lisye Sinaulan; Marssel Michael Sengkey; Avrilie Kapoyos; Jorgen Oliver Kandou; Jonathan Christian Tindas (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to explore the experiences of adolescents who are active Twitter users in building virtual communities as safe spaces. Using a literature review method, this study examines various scholarly sources that discuss adolescent engagement on social media, identity formation, and the dynamics of online communities. The findings indicate that Twitter is used by adolescents not only for social interaction but also as a means of identity exploration and emotional support. The virtual communities formed provide a sense of safety, solidarity, and a space for expression that is often unavailable in offline social environments. However, challenges such as digital toxicity, cyberbullying, and exclusion are also part of the dynamics within these communities. Therefore, a deeper understanding of the role of social media in adolescent life is necessary, along with efforts to strengthen ethical and empathetic digital literacy.